The architecture of computer hardware, systems software, & networking an information technology approach - Englander, Irv; Wong, Wilson (Professor) (Wiley, 2021)
"The subject of this book is the architecture of computer systems. Computer architecture is about the structure and operation of digital computers and computer-based devices. Computer architecture is concerned with the operational methods of the hardware; with the services provided by operating system software; with the acquisition, processing, storage, and output of data; and with the interaction between computer-based devices"--Preface